Developing an all-steel buckling controlled brace. (April 2017) - Seker, Onur; Shen, Jay
Abstract: The development of all-steel tube-in-tube buckling controlled brace (TinT-BCB) is presented. The efficiency of the TinT-BCBs is evaluated experimentally and numerically. The cyclic behavior and fracture life of TinT-BCBs was first investigated through physical testing, followed by FE-based simulations revealing the inherent correlation between fracture and peak cyclic strain in load-bearing braces. The cyclic strain in plastic zones was recorded up to 0.02 strain range during the cyclic tests, enabling the study to use the recorded strain in verifying the FE simulation models. The strain response of plastic zones was captured by the FE simulation up to fracture in conventional large-size braces. The paper concludes that (1) the TinT-BCB, developed based on the buckling-controlling concept, has demonstrated stable and symmetrical cyclic response, with global and local buckling controlled up to 0.035–0.04 story drift ratio; (2) the TinT-BCB is proven to be effective in elongating cyclic fracture life of conventional CBF from 2% SDR to 3.5–4% SDR by adding simple buckling controller. The cost for adding the buckling controller is low in comparison with the substantially increased lateral strength and energy dissipation capacity; and (3) the efficiency of the TinT-BCB in improving overall cyclic behavior in general and elongating fracture life of braces in particular is attributed to its ability in controlling highly concentrated strain in plastic zones of conventional braces. By spreading the concentrated strain demand throughout the entire length, the buckling controller is shown to reduce excessive peak strains in conventional braces by 7–8 times. Highlights: Plastic-zone strain is responsible for fracture. Buckling-controlled brace doubles fracture life of concentrically braced frames.